US Food and Drug Administration (FDA): Benefit-Risk Considerations for Cefiderocol (Fetroja®). (2nd December 2020) - Naseer, Shabnam; Weinstein, Edward A; Rubin, Daniel B; Suvarna, Kalavati; Wei, Xiaohui; Higgins, Karen; Goodwin, Avery; Jang, Seong H; Iarikov, Dmitri; Farley, John; Nambiar, Sumathi
Abstract: In November 2019, the Food and Drug Administration (FDA) approved cefiderocol for the treatment of complicated urinary tract infections (cUTI) including pyelonephritis caused by susceptible gram-negative bacteria in adults with limited to no alternative treatment options based on a randomized, double-blind, noninferiority cUTI trial (APEKS-cUTI). In a randomized, open-label trial (CREDIBLE-CR) in patients with cUTI, nosocomial pneumonia, bloodstream infections, or sepsis due to carbapenem-resistant gram-negative bacteria, an increase in all-cause mortality was observed in patients treated with cefiderocol as compared to best available therapy. The cause of the increased mortality was not established, but some deaths were attributed to treatment failure. Preliminary data from a randomized, double-blind trial (APEKS-NP) in patients with nosocomial pneumonia due to carbapenem-susceptible gram-negative bacteria showed a similar rate of mortality as compared to meropenem. We describe the uncertainties and challenges in the interpretation of the CREDIBLE-CR trial and some benefit-risk considerations for the use of cefiderocol in clinical practice. Clinical Trials Registration : NCT02321800. Abstract : Cefiderocol is approved for the treatment of complicated urinary tract infections (cUTI) based on a single, adequate, and well-controlled cUTI trial. In a trial in carbapenem-resistant infections across body sites, an increase in mortality was observed in cefiderocol-treated patients compared to those treated with best available therapy.